Pedagogical practice and academic performance in mathematical processes: A descriptive - correlational analysis (2020)
This report has aimed to analyze students 'perceptions of pedagogical practice in teachers' mathematical processes and analyze the link with their academic performance. The methodology used is quantitative, articulated with two study analyses, descriptive and correlational, under a non-experimental, correlational-causal cross-sectional design, since it seeks to explain the relationship between the variables. The technique used for data collection was a structured questionnaire, of 47 questions of the Likert Scale type, which was applied to 103 students of the basic education level, belonging to an educational institution located in the “Departamento del Norte de Santander, Colombia”, selected by non-probabilistic sampling This instrument was subjected to the respective analyses that determined its validity and reliability. For the academic performance the average of the accumulated grades obtained at the end of the third academic period, year 2019, was used. The results show that the pedagogical practices on the mathematical processes implemented by the teachers, from the perspective of the students, are a factor in the academic performance of that area.